Coaxial Triple‐Layered versus Helical Be6B11− Clusters: Dual Structural Fluxionality and Multifold Aromaticity - Guo, Jin‐Chang; Feng, Lin‐Yan; Wang, Ying‐Jin; Jalife, Said; Vásquez‐Espinal, Alejandro; Cabellos, José Luis; Pan, Sudip; Merino, Gabriel; Zhai, Hua‐Jin (Angewandte Chemie International Edition, 2017)
Two low‐lying structures are unveiled for the Be6B11− nanocluster system that are virtually isoenergetic. The first, triple‐layered cluster has a peripheral B11 ring as central layer, being sandwiched by two Be3 rings in a coaxial fashion, albeit with no discernible interlayer Be−Be bonding. The B11 ring revolves like a flexible chain even at room temperature, gliding freely around the Be6 prism. At elevated temperatures (1000 K), the Be6 core itself also rotates; that is, two Be3 rings undergo relative rotation or twisting with respect to each other. Bonding analyses suggest four‐fold (π and σ) aromaticity, offering a dilute and fluxional electron cloud that lubricates the dynamics. The second, helix‐type cluster contains a B11 helical skeleton encompassing a distorted Be6 prism. It is chiral and is the first nanosystem with a boron helix. Molecular dynamics also shows that at high temperature the helix cluster readily converts into the triple‐layered one. Fluxional or helical: The Be6B11− cluster is calculated to adopt two competitive conformations. The coaxial triple‐layered cluster mimics the earth–moon system, featuring three‐dimensional structural fluxionality and dual dynamic modes (revolution versus rotation). The helix‐type cluster is the first boron helix; the highly charged boron core presumably governs the helical arrangement.